1983
DOI: 10.1161/01.hyp.5.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous changes in prorenin and renin secretion after captopril in patients with renal artery stenosis.

Abstract: SUMMARY An assay of plasma prorenin was developed in which the conversion to renin occurred under apparently optimal conditions. Some characteristics of the assay were 1) prorenin was activated by Sepharose-bound trypsin at 4°C; 2) the concentration of activator was not critical provided that incubation was prolonged until renin activity had reached a plateau; and 3) this plateau was stable and had the same height as after maximal activation with acid, pepsin, plasmin or urokinase. Maximal activity with Sephar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…Blood samples for plasma renin activity and aldosterone concentrations were taken after 30 min of supine rest. Plasma renin activity was measured by a method based on determining by radioimmunoassay the amount of angiotensin I generated; normal range is 1-12 ng angiotensin I ml Ϫ1 h Ϫ1 (17). Plasma aldosterone was measured with a radioimmunoassay (Coat-aCount; Diagnostic Products, Los Angeles, CA); normal range was 50 -250 pg/ml.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…Blood samples for plasma renin activity and aldosterone concentrations were taken after 30 min of supine rest. Plasma renin activity was measured by a method based on determining by radioimmunoassay the amount of angiotensin I generated; normal range is 1-12 ng angiotensin I ml Ϫ1 h Ϫ1 (17). Plasma aldosterone was measured with a radioimmunoassay (Coat-aCount; Diagnostic Products, Los Angeles, CA); normal range was 50 -250 pg/ml.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…Some authors reported the reciprocal change in active and inactive renin in normal subject (Goldstone et al 1983) and EH or RVH (Glorisso et al 1982;Derkx et al 1983). But others observed no change in inactive renin accompanying an increase in active renin in normal subjects (Millar et al 1980) and in patients with EH or RVH (Linjin et al 1980;Sealey et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Renin and prorenin have long been considered as the separate mediators of tissue and circulating systems (Sealy & Rubattu, 1989). In vitro, when prorenin is acidified at pH 3.3 or exposed to low temperature (< 4˚C) or allowed to interact with antibodies designed from its prosegment sequences (protein-protein interaction), it mediates intrinsic catalytic activity without removal of the prosegment sequence from its N-terminus through a reversible change in conformation (Derkx et al, 1979(Derkx et al, , 1983(Derkx et al, , 1987a(Derkx et al, & b, 1992Pitarresi et al, 1992, Suzuki et al, 2000.…”
Section: The Main Players Associated With Renin Angiotensin Systemmentioning
confidence: 99%